ALTERNATIVE CONSTRUCTIVE HEURISTIC ALGORITHM FOR PERMUTATION FLOW-SHOP SCHEDULING PROBLEM WITH MAKE-SPAN CRITERION - Modrak, Vladimir (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
In this paper, a constructive heuristic algorithm is presented to solve deterministic flow-shop scheduling problem with make-span criterion. The algorithm is addressed to an m-machine and n-job permutation flow shop scheduling problem. This paper is composed in a way that the different scheduling approaches to solve flow shop scheduling problems are benchmarked. In order to compare the proposed algorithm against the benchmarked, selected heuristic techniques and genetic algorithm have been used. Results of experiments show that proposed algorithm gives better or at least comparable solutions than benchmarked constructive heuristic techniques. Finally, the average computational times (CPU time in ms) are compared for each size of the problem.